On charged impurity structures in liquid helium - Pelmenev, A.A.; Krushinskaya, I.N.; Bykhalo, I.B.; Boltnev, R.E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
The thermoluminescence spectra of impurity-helium condensates (IHC) submerged in superfluid helium have been observed for the first time. Thermoluminescence of impurity-helium condensates submerged in superfluid helium is explained by neutralization reactions occurring in impurity nanoclusters. Optical spectra of excited products of neutralization reactions between nitrogen cations and thermoactivated electrons were rather different from the spectra observed at higher temperatures, when the luminescence due to nitrogen atom recombination dominates. New results on current detection during the IHC destruction are presented. Two different mechanisms of nanocluster charging are proposed to describe the phenomena observed during preparation and warm-up of IHC samples in bulk superfluid helium, and destruction of IHC samples out of liquid helium.